Proteolytic processing of class IV chitinase in the compatible interaction of bean roots with Fusarium solani. - Lange, J (1996)
Three chitinase isoenzymes, PvChiE, PvChiF, and PvChiG (molecular masses 29, 28, 27 kD, respectively), were purified from bean (Phaseolus vulgaris L. cv Saxa) roots infected with the fungal pathogen Fusarium solani f. sp. phaseoli, and their amino acid sequence was partially determined. All sequences from all three isoenzymes exactly matched deduced amino acid sequences of the bean class IV chitinase PvChi4, formerly called PR4. The N terminus of PvChif mapped to the hinge region, and the N terminus of PvChiG mapped to the catalytic domain of PvChi4. The N terminus of PvChiE was blocked. The appearance of PvChiE, PvChiF, and PvChiG correlated with an increase in protease activity in infected roots, and they could be generated in vitro by mixing extracts with high protease activity with extracts containing high amounts of PvChi4. Extracts from infected roots prepared in the presence of protease inhibitors also contained the processed forms of PvChi4, indicating that processing occurred in planta and not as an artifact of extraction. Processing of PvChi4 was not detected in incompatible interactions with a nonhost strain of F. solani and in symbiotic interactions with Glomus mosseae, and thus may be important only in compatible interactions with F. solani.